Oxidative stress and blood lipid profile in Cameroonian obese subjects - Oben, Julius E.; Enyegue, Damaris M.; Ngondi, Judith L.; Fomekong, Gilles I. D.; Agbor, Gabriel A. (Sunway University College, 2008)
The relationship between obesity, blood lipids and oxidative stress was investigated in 200 participants. The Body Mass Index of the subjects were positively correlated with the percentage body fat, the systolic and diastolic blood pressure, the fasting blood glucose level, the oxidation of proteins and lipids as well as the concentrations of total and LDL cholesterol. On the other hand, the Body Mass Index was negatively correlated to sulhydryl and protein levels. Obese subjects also had significantly higher body fat (p<.001), waist circumference (p<.001), fasting blood glucose (p<.01) as well as systolic blood pressure (p<.05). Obesity, therefore, can be said to increase the oxidation of plasma proteins and lipids while reducing the antioxidant status as observed by the inverse relation between plasma sulfhydryl groups and the percentage body fat. This increase in oxidative stress can predispose obese people to illnesses such as cardiovascular diseases and diabetes mellitus.